1993
DOI: 10.1163/156856293x00573
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins adsorbed to hemodialyser membranes from heparinized plasma

Abstract: The protein layers formed during contact of plasma with hemodialysis membranes were studied. Dialysers having membranes of cellulose acetate (CA), saponified cellulose ester (SCE), cuprophane (CUP), polymethylmethacrylate (PMMA), and polyacrylonitrile (PAN) were used. Heparinized human plasma was recirculated through the dialysers for four hours. They were then rinsed and the proteins adsorbed to the membranes were eluted with 2% SDS. The yields of protein from the different membranes increased in the order: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Cornelius and Brash [43] demonstrated that C3 was present in SDS eludates after plasma incubations of a number of hemodialysis membranes. In accordance with this, we show in the present study that SDS has a dramatic washing effect on different complement activator surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Cornelius and Brash [43] demonstrated that C3 was present in SDS eludates after plasma incubations of a number of hemodialysis membranes. In accordance with this, we show in the present study that SDS has a dramatic washing effect on different complement activator surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced SDS PAGE (12% gels) and immunoblot analysis were performed on the eluted proteins. 61 The proteins were transferred to immobilon PVDF membranes (Millipore, Bedford, MA) and stained using a stabilized gold sol (Protogold, Cedarlane Laboratories, Hornby, Ontario, Canada). Primary antibodies to various plasma proteins, the majority of which were in the form of fractionated antisera developed in goats were used at a dilution of 1:1000.…”
Section: Sds Page and Immunoblottingmentioning
confidence: 99%
“…The blots for the surfaces are much less complex than that for plasma itself, 27 suggesting some selectivity in their interactions with the plasma proteins. The gold surface shows virtually no proteins except for trace amounts of albumin, IgM, C3c, and complement factor I.…”
Section: Protein Interactionsmentioning
confidence: 99%